2016
DOI: 10.1128/jvi.02976-15
|View full text |Cite
|
Sign up to set email alerts
|

New Mechanism of Hepatic Fibrogenesis: Hepatitis C Virus Infection Induces Transforming Growth Factor β1 Production through Glucose-Regulated Protein 94

Abstract: Hepatic fibrosis is a critical step in liver cirrhosis caused by hepatitis C virus infection. It is already known that immune cells, including Kupffer cells, mediate liver fibrosis. Recently, several papers have suggested that HCV-infected hepatocytes also significantly produce TGF-β1. Here, we provide the first examination of TGF-β1 levels in the hepatocytes of HCV patients. Using an HCV culture system, we showed that HCV infection increases TGF-β1 production in hepatocytes. Furthermore, we confirmed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 49 publications
(72 reference statements)
0
32
0
Order By: Relevance
“…Molecular mechanisms of hepatic fibrogenesis have been studied using several culture models, in which culture supernatants of hepatocyte‐derived cells with or without stimuli including HCV protein expression were transferred to HSC culture or in which both types of cells were co‐cultured under direct contact or noncontact conditions . In HCV‐mediated fibrogenesis, up‐regulation of fibrogenic factors was reported in a co‐culture of HSCs with HCV Core‐expressing cells, and TGF‐β1 secreted from the E2‐expressing cells activated the HSCs . HCV/human immunodeficiency virus co‐exposure in hepatocytes and HSC revealed cooperative transcriptional activation of profibrotic pathways .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular mechanisms of hepatic fibrogenesis have been studied using several culture models, in which culture supernatants of hepatocyte‐derived cells with or without stimuli including HCV protein expression were transferred to HSC culture or in which both types of cells were co‐cultured under direct contact or noncontact conditions . In HCV‐mediated fibrogenesis, up‐regulation of fibrogenic factors was reported in a co‐culture of HSCs with HCV Core‐expressing cells, and TGF‐β1 secreted from the E2‐expressing cells activated the HSCs . HCV/human immunodeficiency virus co‐exposure in hepatocytes and HSC revealed cooperative transcriptional activation of profibrotic pathways .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of mechanisms by which HCV infection induces TGF‐β expression or activates the TGF‐β pathway have been carried out. For example, expression of HCV Core or E2 contributes to an increase in expression and secretion of TGF‐β, and increased levels of reactive oxygen species (ROS) caused by HCV infection are involved in TGF‐β production . Another study has shown that the HCV nonstructural (NS) 3 potentially mimics TGF‐β2 and functions through binding to TGF‐β receptor I …”
mentioning
confidence: 99%
“…23 Recently, Jee found high levels of expressing TGF-β in hepatocytes of HCV patients, as well as, in HCV-infected hepatocytes cultured in vitro, as that of cultured cells was sufficient to activate liver fibrosis-associated cells, hepatic stellate cells (HSC), a new mechanism underlying liver fibrogenesis. 24 Accordingly, the HCV E2 protein was reported as cause of this overproduction, by acting through glucose-regulated protein 94 (GRP94) mediated NF-κB activation, which proposed GRP94 as a potential target for preventing HCV-caused liver cirrhosis. Relevant in this regard, other investigations have shown an upregulated level of TGF-β either directly by HCV factors, in particular core protein, or via NF-κB and oxidative/ER stress activation.…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…The Huh-7 cells were provided by Dr Sung Key JANG (Department of Life Sciences, Pohang University of Science and Technology (POSTECH), Korea) [35] . Both the HepG2 and Huh-7 cells were cultured in DMEM (Gibco, Waltham, MA, USA) supplemented with 10% fetal bovine serum (ATCC) and 5% penicillin-streptomycin (Gibco).…”
Section: Cell Culturementioning
confidence: 99%